2014
DOI: 10.4049/jimmunol.1303380
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins Limit Macrophage Necroptosis through Cleavage of Rip1 Kinase

Abstract: It has recently been shown that programmed necrosis, necroptosis, may play a key role in the development of inflammation. Deciphering the regulation of this pathway within immune cells may therefore have implications in pathology associated with inflammatory diseases. We show that treatment of macrophages with the pan caspase inhibitor (zVAD-FMK) results in both increased phosphorylation and decreased cleavage of receptor interacting protein kinase-1 (Rip1), leading to necroptosis that is dependent on autocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…S6). Our recent work with recombinant Rip1 also confirms the specificity of the Rip1 antibody used here (52).…”
Section: Generation Of Macrophages Andsupporting
confidence: 82%
“…S6). Our recent work with recombinant Rip1 also confirms the specificity of the Rip1 antibody used here (52).…”
Section: Generation Of Macrophages Andsupporting
confidence: 82%
“…[39][40][41] Cathepsin B was shown to regulate various immune functions; for example, persistence of memory T cells, antigen-presenting function of dendritic cells, monocyte and macrophage necrosis/necroptosis and TLR signalling. [42][43][44][45][46] The publicly available data on human monocytes and lymphoblastoid cell lines (see online supplementary table S3) have suggested cell type-specific effects/functions of the 8p23 SNPs as also supported by a recent BLK study. 47 Guthridge et al 47 performed a comprehensive analysis of the FAM167A-BLK subregion, which has revealed two functional variants that regulate alternative promoter activities in cell type-specific and developmental stage-specific manners.…”
Section: Discussionmentioning
confidence: 63%
“…Conversely, indigestible lysosomal crystals can destabilize lysosomal membranes, release lysosomal enzymes into cytosol causing cell stress to engage autophagic tubular cell death. Some of the lysosomal enzymes – e.g., cathepsin B – are reported to activate necroptosis by cleaving the necroptosis inhibitor protein RIPK1 in immune cells [26]. In fact, crystals of calcium oxalate, calcium phosphate, calcium pyrophosphate, cysteine, cholesterol, and MSU induced tubular cell necroptosis in vitro by engaging RIPK3 and pseudokinase MLKL [5, 6] (Fig.…”
Section: Type 2 Crystalline Nephropathy: Intratubular Crystal Formationmentioning
confidence: 99%